الكنيسة في مملكة بيت المقدس عصر الحروب الصليبية الدور والواجبات (1099 – 1187) - محمد, فتحي عبد العزيز; صالح محمد, أشرف سيد (Sciences de l'Homme et de la Société, 2014)
موضوع هذه الدراسة هو واجبات الكنيسة في مملكة بيت المقدس اللاتينية منذ قيام المملكة 1099 وحتى استرداد بيت المقدس على يد صلاح الدين الأيوبي 1187. وذلك للتعرف على دور الكنيسة وطبيعته، وأهدافه، حتى يمكن تقدير حجمه، ومعرفة أثره. مع  تناول التواجد الكنسي اللاتيني في الأرض المقدسة، حيث أن الفترة التي يعرض لها البحث تمثل المرحلة الهامة في تاريخ الكنيسة اللاتينية فقد كانت مرحلة خصبة تعددت فيها أعمال وأنشطة وعلاقات الكنيسة.     The subject of thisstudy isthe role of the Church in Latin kingdom of Jerusalem, since the establishment of the Kingdom 1099, and even recover Jerusalem by Saladin 1187.To identify the role of the Church, it’s objectives, impact, and achievements that has had a direct impact on the future of the crusading movement.In addition to showcasing ecclesiastical Latin presence in the Holy Land,where period of the study represents an important stage in the history of the Latin Church. It was a fertile phase; there was many Works, activities and relations of the church.